Techno-Economic Felling Cycles for Selected Energy Plantation Species in the Arid Areas of Western Rajasthan - Kalla, Jagdeesh C; Chand, Gyan; Vyas, D L; Gehlot, N S (Annals of Arid Zone, 2016)
Felling cycles for fuel were evaluated for four desert tree species, viz., Acacia tcrtilis, Albizzia lebbek, Acacia nilotica and Azadirachta indica. The study revealed that by employing requisition techniques the physical maxima of fuel yield per tree for Alibizzia lebbek, Acaciu torttlis, Azadirachta indica and Acacia nilotica were realised after 14th year (15 kg), 25th year (39 kg), 50th year (5t kg) and 13th year (6 kg) since the formation of these tree stands. Subjecting these to ammortized cost - revenue constraints, the economic optima came out to be II years for Albizzia lebbek yielding 6 kg/ tree, 8 years yielding 20 kg/tree for Acacia tortilis, 24 kg/tree on 23 year for Azadiarchta indica and imaginary yield in 49th year for Acacia nilotica. Considering the maximum fuel yield within minimum time period and the maximum returns, Acacia tortilis was found to exceed all the tree species under consideration.